2013
DOI: 10.1111/epi.12196
|View full text |Cite
|
Sign up to set email alerts
|

Lacosamide treatment following status epilepticus attenuates neuronal cell loss and alterations in hippocampal neurogenesis in a rat electrical status epilepticus model

Abstract: and †CNS Research, UCB Pharma, Braine L'Alleud, Belgium SUMMARY Purpose: The antiepileptic drug, lacosamide, exerts its therapeutic activity by enhancing slow inactivation of voltage-gated sodium channels. Because putative preventive or disease-modifying effects of drugs may affect epileptogenesis, intrinsic severity, and comorbidities, it is of particular interest to assess the effect of lacosamide on the development of epilepsy and associated cellular alterations. Methods: The effect of lacosamide was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 41 publications
2
17
1
Order By: Relevance
“…C. Rates of interictal spikes from day 4 to day 14 after SE in controls and in LCM-treated animals, in CA3 and subiculum (* p < 0.05, ** p < 0.01) (vertical dotted lines define the peak of seizure occurrence in control animals). study found a neuroprotective effect of LCM on hippocampal and parahippocampal structures when administered after a SE induced with prolonged stimulation of the basolateral amygdala, without however any effect on the duration of the latent period (Licko et al, 2013). Although the methods used to monitor seizures are different between the study of Licko et al (2013) and our study, these results highlight the need for additional studies addressing the potential disease-modifying properties of LCM.…”
Section: Discussioncontrasting
confidence: 48%
“…C. Rates of interictal spikes from day 4 to day 14 after SE in controls and in LCM-treated animals, in CA3 and subiculum (* p < 0.05, ** p < 0.01) (vertical dotted lines define the peak of seizure occurrence in control animals). study found a neuroprotective effect of LCM on hippocampal and parahippocampal structures when administered after a SE induced with prolonged stimulation of the basolateral amygdala, without however any effect on the duration of the latent period (Licko et al, 2013). Although the methods used to monitor seizures are different between the study of Licko et al (2013) and our study, these results highlight the need for additional studies addressing the potential disease-modifying properties of LCM.…”
Section: Discussioncontrasting
confidence: 48%
“…Furthermore, histological analysis revealed no difference in the extent of neurodegeneration, axonal injury, or hilar neuron loss within the hippocampus of lacosamide-treated rats compared to vehicle treatment. Recently, Licko and colleagues sought to expand previous reports on the anti-epileptogenic potential of lacosamide following status epilepticus [81]. To avoid any possible interference with the induction of sustained SE, lacosamide treatment began following its cessation and was continued for 23 days.…”
Section: Therapeutic Potential Of An Interaction Between Crmp2 and Lamentioning
confidence: 99%
“…Despite the impact on molecular changes induced by SE and contrary to previous reports, lacosamide treatment did not successfully prevent the development of SRS. Additionally, latency to first seizure and the frequency of spontaneous seizures were not attenuated by chronic lacosamide treatment [81]. While the treatment paradigm was somewhat unorthodox, combining oral administration and continuous infusion via osmotic minipump, it is unlikely that this would account for the lack of efficacy in preventing the development of spontaneous seizures.…”
Section: Therapeutic Potential Of An Interaction Between Crmp2 and Lamentioning
confidence: 99%
“…Furthermore, (S)-LCM is unlikely to affect hippocampal cell death as a recent study demonstrated that the parent compound (R)-LCM does not alter neuronal survival following TBI (Pitkanen et al, 2014). The lack of significant separation between (S) -LCM- and vehicle-treated groups may be a result of the nature of administration, despite the previous success observed with infusion of (R) -LCM in a separate study (Licko et al, 2013). While continuous subcutaneous infusion was considered to be preferable over daily intraperitoneal injections, it is possible that inflammation at the implantation site may have been a factor.…”
Section: Discussionmentioning
confidence: 89%